Opportunities of Nomadic Space: Sound of Paper Collectors in Istanbul - Geçkili Karaman, Pınar; Salgamcioglu, Mehmet (Enquiry The ARCC Journal for Architectural Research, 2025)
The metropolitan city is characterized by a state of perpetual transformation, fostering a nomadic existence shaped by spatial mobility. This ongoing cycle of destruction and reconstruction generates “nomadic spaces,” where urban landscapes remain in flux. Beyond its spatial dynamics, the metropolis is also defined by the direct migration of people, particularly marginalized groups, who navigate and reshape the urban environment. Among these groups, paper collectors in Istanbul play a critical yet often overlooked role in the city’s recycling system. Despite their substantial contribution to urban sustainability, their work remains largely informal and is usually coded as illegal, positioning them as subaltern actors within the urban fabric. This study examines the spatial practices and lived experiences of paper collectors, framing their activities as a form of urban act embedded within the ever-evolving nature of the metropolis. The primary aim of this article is to explore the mechanisms of existence in the nomadic city by deconstructing the language of paper collectors, who are represented as subalterns, using verbal and spatial instruments and deriving, multiplying, and articulating the subaltern, making their voices heard. Employing a mixed-method approach that integrates ethnography and grounded theory, the study utilizes qualitative data collection techniques, including participant observation of daily routes, in-depth interviews, and spatial analysis of warehouses where collectors work and live. The analysis and diagramatization of the data were conducted using MAXQDA software. Through this multi-layered analysis, the paper collectors deconstruct the spatial and experiential dimensions of subaltern urban actors, offering new insights into the intersection of informality, mobility, and sustainability in the contemporary city.